Uso de GeoGebra en el aprendizaje de sistema de ecuaciones lineales en décimo año de la Unidad Educativa Amelia Gallegos - Moyolema Naula, Sara Lucia (2023)
The study of mathematics has been one of the challenges faced by primary and secondary students due to the lack of motivation and the absence of the use of didactic resources such as dynamic software, interactive games, and others; that is the reason why currently, teachers and students are forced to use and promote technological tools to facilitate learning. The objective of this investigation is to determine the incidence of the use of GeoGebra in learning the system of linear equations in the tenth-year students of the "Amelia Gallegos" high school, period 2022-2023. A quantitative approach methodology of an explanatory and applicative level was used with a pre-experimental design. All tenth-year classes represent the population; however, we worked with a sample of 30 students of the parallel "A" of the mentioned High School. For data collection, an objective test was used (Pre-test - Post-test); the results obtained through the t-Student statistic determined that the use of GeoGebra positively affects the learning of the system of linear equations through the application of theoretical and practical classes. It is concluded that the use of GeoGebra is one of the alternative tools to face the difficulties that students have in the learning process in the area of mathematics since this dynamic software significantly improves their knowledge of the system of linear equations. For this reason, using GeoGebra is recommended in learning the system of linear equations as didactic material that helps teachers and students improve their mathematical skills and competencies.